CHORIORETINAL ATROPHY IN VITREORETINAL LYMPHOMA: Risk Factors and Visual Outcomes. Issue 3 (March 2022) - Marchese, Alessandro; Cicinelli, Maria VITTORIA; Cavalleri, Michele; Bandello, Francesco; Modorati, Giulio; Miserocchi, Elisabetta
Abstract : Purpose: To investigate the frequency, risk factors, and functional prognosis of chorioretinal atrophy (CRA) in vitreoretinal lymphoma (VRL). Methods: This was a retrospective cohort study of consecutive patients with vitreoretinal lymphoma. The demographic, clinical, and retinal features and the treatment modalities of each patient were collected. The charts and the multimodal imaging at each visit were reviewed. The risk factors associated with CRA were investigated with a mixed-model Cox regression. Results: Of the 79 eyes of 40 patients included, 41 eyes (52%) had CRA; 27 and 14 eyes had focal and diffuse CRA, respectively. The rate of vitreoretinal lymphoma lesions in the macula was similar between focal and diffuse CRA (96% vs. 93%). The eyes with CRA had worse best-corrected visual acuity ( P = 0.006) than eyes with no CRA; diffuse atrophy had the worst best-corrected visual acuity ( P < 0.001). The presence of retinal infiltrates (hazard ratio = 3.75, 95% confidence interval [CI] 1.46–9.59, P = 0.006) and vertical hyperreflective lesions (hazard ratio= 4.13 95% CI 1.14–14.93, P = 0.03) on optical coherence tomography and macular involvement (hazard ratio = 6.59, 95% CI 1.41–30.53, P = 0.02) were associated with a higher risk of CRA. Conclusion: Vitreoretinal lymphoma presenting with retinal infiltrates and macular involvement carried a higher risk of CRA. Risk factors for CRA should be identified for the potential of severe visual loss. Prompt diagnosis of vitreoretinal lymphoma may allow better control of the disease. Abstract : This study revealed the frequency, risk factors, and functional prognosis of chorioretinal atrophy associated with vitreoretinal lymphoma.